2018
DOI: 10.1177/1729881418754563
|View full text |Cite
|
Sign up to set email alerts
|

Power-minimization and energy-reduction autonomous navigation of an omnidirectional Mecanum robot via the dynamic window approach local trajectory planning

Abstract: To improve the energy efficiency of the Mecanum wheel, this article extends the dynamic window approach by adding a new energy-related criterion for minimizing the power consumption of autonomous mobile robots. The energy consumption of the Mecanum robot is first modeled by considering major factors. Then, the model is utilized in the extended dynamic window approach-based local trajectory planner to additionally evaluate the omnidirectional velocities of the robot. Based on the new trajectory planning objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 19 publications
(29 reference statements)
0
30
0
Order By: Relevance
“…Many research works have achieved the goal of saving energy through trajectory optimization [20][21][22]. Xie.…”
Section: Of 15mentioning
confidence: 99%
See 2 more Smart Citations
“…Many research works have achieved the goal of saving energy through trajectory optimization [20][21][22]. Xie.…”
Section: Of 15mentioning
confidence: 99%
“…Their results showed that following the same straight-line path via different velocity profiles consumed different amounts of energy. However, their studies were restricted to straight-line paths and stationary states in the beginning and at the end, and hence became less practical for autonomous navigation [21]. Bartlett et al proposed a probabilistic, data-driven approach to estimating the energy consumption of a mobile robot on a set of trajectories, whether they have been traversed or not.…”
Section: Of 15mentioning
confidence: 99%
See 1 more Smart Citation
“…So, the energy consumption of MRs comes from four subsystems of MR: Motion system, control system, sensor system, and communication system, as shown in Figure 2. After the energy model of MR is formulated [18][19][20], the power consumption of the four robotic subsystems can be calculated by the power consumption model. By establishing the relationship between the power consumption of each subsystem, the optimal algorithm to reduce the energy consumption of the robot can be obtained [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is of great significance to study the energy consumption of the mobile robots, and energy-saving strategies have been conducted by many researchers via different aspects, for example, trajectory planning [4][5][6], motion control [7,8], and mechanical design [9]. In order to study the energy-efficient strategies, a detailed and accurate energy consumption model needs to first be established for the robot system.…”
Section: Introductionmentioning
confidence: 99%